Functional and Structural Alterations in the Cingulate Motor Area Relate to Decreased Fronto-Striatal Coupling in Major Depressive Disorder with Psychomotor Disturbances - Liberg, Benny; Klauser, Paul; Harding, Ian H.; Adler, Mats; Rahm, Christoffer; Lundberg, Johan; Masterman, Thomas; Wachtler, Caroline; Jonsson, Tomas; Kristoffersen-Wiberg, Maria; Pantelis, Christos; Wahlund, Björn (Frontiers in Psychiatry, 2014)
Psychomotor disturbances are a classic feature of major depressive disorders. These can manifest as lack of facial expressions and decreased speech production, reduced body posture and mobility, and slowed voluntary movement. The neural correlates of psychomotor disturbances in depression are poorly understood but it has been suggested that outputs from the cingulate motor area (CMA) to striatal motor regions, including the putamen, could be involved. We used functional and structural magnetic resonance imaging to conduct a region-of-interest analysis to test the hypotheses that neural activation patterns related to motor production and gray matter volumes in the CMA would be different between depressed subjects displaying psychomotor disturbances (n=13) and matched healthy controls (n=13). In addition, we conducted a psychophysiological interaction analysis to assess the functional coupling related to self-paced finger-tapping between the caudal CMA and the posterior putamen in patients compared to controls. We found a cluster of increased neural activation, adjacent to a cluster of decreased gray matter volume in the caudal CMA in patients compared to controls. The functional coupling between the left caudal CMA and the left putamen during finger-tapping task performance was additionally decreased in patients compared to controls. In addition, the strength of the functional coupling between the left caudal CMA and the left putamen was negatively correlated with the severity of psychomotor disturbances in the patient group. In conclusion, we found converging evidence for involvement of the caudal CMA and putamen in the generation of psychomotor disturbances in depression.